2006
DOI: 10.1007/s11145-005-4713-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Cognitive and Linguistic Abilities that Influence the Reading Comprehension Skills of Children from Diverse Linguistic Backgrounds

Abstract: This study investigated the influence of cognitive and linguistic skills on the reading comprehension performance of a group of learners from diverse linguistic backgrounds. The study also compared the reading comprehension performance of grade 4 children who entered kindergarten with little or no experience with English (ESL) to that of a group of native English speakers. Examiners administered various tasks of reading, language, and memory to the children in the study (n=480). The sample included three compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
95
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(113 citation statements)
references
References 53 publications
14
95
3
1
Order By: Relevance
“…Although links between syntactic knowledge and reading comprehension have been established for monolingual speakers, less work has been conducted examining the role of syntax in reading comprehension in L2 learners. However, findings from the limited number of studies that have examined the contributions of syntax to reading comprehension among L2 learners are consistent with findings from studies examining these skills in native English speakers (e.g., Lesaux, Lipka, & Siegel, 2006;Lipka & Siegel, 2012). Children who were L2 learners performed worse on syntactic awareness measures than native English speakers (Lesaux et al, 2006).…”
Section: Syntactic Knowledgesupporting
confidence: 69%
See 1 more Smart Citation
“…Although links between syntactic knowledge and reading comprehension have been established for monolingual speakers, less work has been conducted examining the role of syntax in reading comprehension in L2 learners. However, findings from the limited number of studies that have examined the contributions of syntax to reading comprehension among L2 learners are consistent with findings from studies examining these skills in native English speakers (e.g., Lesaux, Lipka, & Siegel, 2006;Lipka & Siegel, 2012). Children who were L2 learners performed worse on syntactic awareness measures than native English speakers (Lesaux et al, 2006).…”
Section: Syntactic Knowledgesupporting
confidence: 69%
“…However, findings from the limited number of studies that have examined the contributions of syntax to reading comprehension among L2 learners are consistent with findings from studies examining these skills in native English speakers (e.g., Lesaux, Lipka, & Siegel, 2006;Lipka & Siegel, 2012). Children who were L2 learners performed worse on syntactic awareness measures than native English speakers (Lesaux et al, 2006). However, within the groups, poor comprehenders performed worse than good comprehenders (Lipka & Siegel, 2012).…”
Section: Syntactic Knowledgesupporting
confidence: 68%
“…In some school contexts, linguistic background could also be a factor. In a recent study, Lesaux, Lipka & Siegel (2006) found that native English-speaking children achieved significantly higher scores on syntactic awareness and verbal working memory than ESL children. Whether this advantage could be partially offset by syntactic awareness training specifically for ESL students remains to be investigated.…”
Section: Reading and Writingmentioning
confidence: 96%
“…In particular, there is evidence that word-level reading and reading comprehension skills are highly correlated in L2 learners, just as they are in monolinguals (Chiappe, Siegel, & Wade-Woolley, 2002;Lesaux, Lipka, & Siegel, 2006;van Gelderen et al, 2004;Verhoeven, 2000), and that word reading fluency (conceptualized in terms of accuracy and speed) correlates with reading comprehension (e.g., van Gelderen et al, 2004).…”
Section: Considering a Longitudinal Expanded Mediation Svr Frameworkmentioning
confidence: 99%